Effects of Detention for Flooding Mitigation under Climate Change Scenarios— Implication for Landscape Planning in the Charles River Watershed, Massachusetts, USA - Chingwen Cheng; Elizabeth A Brabec; Yi-Chen E Yang; Robert L Ryan (Fábos Conference on Landscape and Greenway Planning, 2013)
Climate change has posed increased risks to environmental hazards (e.g., flooding, droughts, hurricanes) in addition to new challenges under climate change impacts (e.g., early snow melt, sea level rises, heat waves). Floods are omnipresent in almost every city in the United States and account for the most economic losses than any other single geophysical hazard (White and Haas 1975). Previous climate change studies have suggested promising trends of increasing temperature and changing precipitation patterns as well as increased intensity and duration of storm events that are likely to result in more flooding events in the Northeast region. Flooding mitigation strategies have been focusing on structured engineering solutions such as dams and dikes along streams and rivers since the late 1910s. In recent decades, in lieu of conventionally engineered infrastructure, scholars have called for “soft” strategies such as green infrastructure (Thomas and Littlewood 2010) and land use planning (Burby 1998; Godschalk 2004) for comprehensive hazard mitigation and stormwater management integrated into planning and design interventions for flooding mitigation. Stormwater detention is among the most prevalent stormwater management practices for flooding mitigation; however, the perceived benefits could be overestimated without empirical study (Beecham et al. 2005). In addition, planners are now facing challenges to cope with uncertainties from climate change impacts under a paradox between making room for water while managing growth in land use planning. For local planners and stakeholders to make adaptive land use decisions for climate change, this paper aims to answer two key questions: (1) to what degree and in what way does climate change have impacts on long-term flooding hazards? (2) how much detention area in the watershed would be needed for mitigating flooding hazards induced by climate change? And what do the results imply for innovations in landscape planning?
Keywords: greenways; climate change; flooding; landscape; planning; charles river; watershed; massachusetts